The Modified Japanese Orthopaedic Association Scale: Establishing Criteria for Mild, Moderate, and Severe Disease in Patients with Degenerative Cervical Myelopathy. Issue 1 (April 2016) - Tetreault, Lindsay; Nouri, Aria; Singh, Anoushka; Bartels, Ronald; Kopjar, Branko; Arnold, Paul; Fehlings, Michael
Introduction: The modified Japanese Orthopaedic Association (mJOA) score is a validated, investigator-administered tool used to evaluate functional status in patients with degenerative cervical myelopathy (DCM). This scale is increasingly used in this population to measure baseline myelopathy severity, postoperative improvements and social independence. There is, however, no study that determines what scores on the mJOA constitute mild, moderate and severe disease. Patients in different severity categories are managed differently both intraoperatively and postoperatively; therefore, establishing this criteria has clinical value across the whole spectrum of care. This study aims to determine appropriate cut-offs between mild, moderate and severe myelopathy and to examine the construct validity of these definitions. Material and Methods: Between December 2005 and January 2011, 757 patients with clinically-diagnosed and imaging-confirmed CSM were enrolled in either the prospective, multicenter CSM-North America (n=278) or CSM-International (n=479) study at 26 global sites. Functional status and quality of life were evaluated in these patients at baseline and at 6-, 12- and 24-months postoperative using a wide variety of outcome measures, including the mJOA, Nurick score, Neck Disability Index (NDI) and Short-form-36 (SF-36). Using the Nurick grade as an anchor, ROC analysis was conducted to determine the cut-offs between mild and moderate myelopathy and between moderate and severe disease. These cut-offs were validated by developing and testing various constructs. Specifically, we examined whether patients in different severity groups had significantly different functional impairment, disability, symptomatology, imaging findings and post-treatment improvements. Finally, members of AOSpine International were surveyed to see what professionals viewed as appropriate cut-offs between severity categories. Results: In ROC analysis, a mJOA of 14 was determined to be the cut-off between mild and moderate myelopathy and a score of 11 as the score between moderate and severe disease. Patients in the severe myelopathy group (n=254) had significantly reduced quality of life and functional status and a greater number of signs and symptoms than patients classified as mild (n=193) or moderate (n=296). Furthermore, severe patients required greater improvements on the mJOA to achieve a minimum clinically important difference. From our survey, a score of 15 (n=143, 34.38%) was the most commonly selected cut-off between mild and moderate myelopathy (mean 14.38). The majority of respondents selected 10 (n=178, 42.79%) as the mJOA cut-off between moderate and severe myelopathy (mean 11.26) Conclusion: Based on our results, mild myelopathy can be defined as a mJOA=15-17, moderate as mJOA=12-14 and severe as mJOA < 12. These categories are the same as those established by the AOSpine study group for the purpose of the CSM-North America study.